Increased substrate oxidation and mitochondrial uncoupling in skeletal muscle of endurance-trained individuals - Befroy, D. E.; Petersen, K. F.; Dufour, S.; Mason, G. F.; Rothman, D. L.; Shulman, G. I. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Endurance exercise training is accompanied by physiological changes that improve muscle function and performance. Several studies have demonstrated that markers of mitochondrial capacity are elevated, however, these studies tend to be performed ex vivo under conditions that yield maximal enzyme activities or in vivo but monitoring the response to exercise. Therefore, it is unclear whether basal mitochondrial metabolism is affected by exercise training. To explore whether resting muscle metabolism was altered in trained individuals in vivo, two independent parameters of metabolic function—tricarboxylic acid (TCA) cycle flux (VTCA), and ATP synthesis (VATP)—were assessed noninvasively by using magnetic resonance spectroscopy in a cohort of young endurance trained subjects (n = 7) and a group of matched sedentary subjects (n = 8). VTCA was 54% higher in the muscle of endurance trained compared with sedentary subjects (91.7 ± 7.6 vs. 59.6 ± 4.9 nmol/g/min, P < 0.01); however, VATP was not different between the trained and sedentary subjects (5.98 ± 0.43 vs. 6.35 ± 0.70 ?mol/g/min, P = 0.67). The ratio VATP/VTCA (an estimate of mitochondrial coupling) was also significantly reduced in trained subjects (P < 0.04). These data demonstrate that basal mitochondrial substrate oxidation is increased in the muscle of endurance trained individuals yet energy production is unaltered, leading to an uncoupling of oxidative phosphorylation at rest. Increased mitochondrial uncoupling may represent another mechanism by which exercise training enhances muscle insulin sensitivity via increased fatty acid oxidation in the resting state.